Arap dilinde tazmin ve Kur’an-ı Kerim’de kullanılışı - Taş, Süleyman (My University, 2015)
Tazmîn, lügatta; ‘bir şeyi bir şeye katmak, onun içine koymak’ demektir. Arap dilinde tazmîn birkaç ilim dalında söz konusudur. Bunlardan biri de nahiv ilmidir. Çalışmamız giriş ve iki bölümden oluşmaktadır. Giriş bölümünde; tazmînin Arap dilindeki anlamları kısaca verilip, örneklerle açıklanmıştır. Birinci bölümde; asıl konumuz olan nahiv ilmindeki tazmîn genişçe incelenmiş, tanımı, gayesi ve çeşitleri açıklanmış ve felsefesine de yer verilip tazmîn hakkında sorulması muhtemel sorulara cevap aranmaya çalışılmıştır. İkinci bölümde; tazmîn sanatının etkisi ve manaya katkısı Kur’ân-ı Kerim’den birçok örneklerle anlatılmıştır. Bunu yaparken de okuyucuyu bıktırmamak amacıyla benzer örneklerin sadece biriyle yetinilmiş ve aynı kalıpta gelen ayetler tekrarlanmamıştır. Sonuç kısmında ise tazmîn sanatına vâkıf olmanın Kur’ân’ı anlamada ne denli önemli olduğu kanaatına varıldığı vurgulanmıştır. tazmîn, fiillerin tazmîni, tazmîn-i nahvî, harf-i cer, Kur’ân-ı Kerîm.

The implication (semantic saturation) dictionary meaning is ‘to add a something into another thing or to put a something inside another thing’. In Arabic language implication has got meaning of word in several science branches. One of these is named as ‘implication in syntax’. Our study is formed as introduction and two parts. In the beginning of our study, the meanings of implication which are used in Arab language are explained shortly and expressed with examples. In part one, our real subject which is The implication in the science of syntax, has been deeply studied and after explaining its meaning, role and its kinds, we have discussed on its philosopy and tried to find asnwers to possible questions which could possibly be asked. In part two, The effects of implication art and its contrubitions to meaning has been studied and explained briefly with many examples of verses from Qoran. In order to not let the readers get bored, we have only showed one example in between similar examples and we did not dublicate the similar format verses of Qoran as well. At the end of our study, we have emphasized the importance of controling the art of implication in understanding the meaning of Qoran. Key words: tazmeen, verb’s tazmeen, implication, semantic saturation, preposition, Holy Qoran.
Keywords: Arap dili